1995
DOI: 10.1115/1.2794210
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Vertebral Strain Measurements Under Axial and Eccentric Loading

Abstract: The mid to lower cervical spine is a common site for compression related injury. In the present study, we determined the patterns of localized strain distribution in the anterior aspect of the vertebral body and in the lateral masses of lower cervical three-segment units. Miniature strain gages were mounted to human cadaveric vertebrae. Each preparation was line-loaded using a knife-edge oriented in the coronal plane that was moved incrementally from anterior to posterior to induce compression-flexion or compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(20 citation statements)
references
References 16 publications
2
18
0
Order By: Relevance
“…Our surface strain results are consistent with the literature on lumbar vertebral body surface strains and they were found to result from predictable loading patterns [6,19,60]. Frei et al found axial principal strains of 700-to-840 microstrain for 500 N applied load compared with 582 microstrain (mean) for 400 N applied in the present study.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…Our surface strain results are consistent with the literature on lumbar vertebral body surface strains and they were found to result from predictable loading patterns [6,19,60]. Frei et al found axial principal strains of 700-to-840 microstrain for 500 N applied load compared with 582 microstrain (mean) for 400 N applied in the present study.…”
Section: Discussionsupporting
confidence: 95%
“…This is a trivial task for traditional engineering materials with known geometry, but the application of these methods to the biologic tissues of the lumbar spine is novel. Surface strains on vertebrae have been measured previously [6,19,60]; however, these strains have not been directly correlated with spinal loading and equated with disc health. We have measured distinct relationships between vertebral body surface strain (principal strains) and spinal segment loading (force/moment).…”
Section: Discussionmentioning
confidence: 98%
“…This study did not quantify the level or degree of validation, a process used in the present study. Furthermore, unlike cervical spine experiments wherein strain data on vertebral body and facet joint have been measured under different loading conditions [26], in the lumbosacral spine, moment-rotation curves appear to be the only response finite element modelers have used for validation. Therefore, it is critical to match these curves as closely as possible during the validation process.…”
Section: Validation Processmentioning
confidence: 98%
“…The discs and their adjacent vertebral segments have articulating surfaces that are designed to absorb and distribute force under compressive loads. Loads transfer anteriorly through the vertebral body and disc and posteriorly through the facets and lateral masses (Pintar, 1995). There are bending moments and shear forces that accompany various movements and create increased mechanical challenges to the spine.…”
Section: Mechanical Risks Of Headstandmentioning
confidence: 99%